Remarks at Opening Press Conference, World Bank/IMF Spring Meetings, Washington, DC, April 16, 2015 - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group, discusses promoting strong economic growth in developing countries. He speaks about the need to invest in people, especially in education, health and to build social safety nets and protections against both natural disasters and pandemics to ensure that people don't remain trapped in extreme poverty. He talks about the challenges in trying to work in all kinds of complex political situations, so that whatever happens to be going on in the political sphere, we can continue to work to lift people out of poverty and boost shared prosperity. He talks about multilateralism that is always complicated and is always fraught with disagreements. He promises to continue to try to engage with governments to have that impact. He mentioned reports released about the Bank’s resettlement history. The transcript includes the Q&A session.